Global Mental Health in Our Own Backyard: An Unaccompanied Immigrant Child's Migration From El Salvador to New York City. Issue 8 (23rd August 2016) - Baily, Charles D. R.; Henderson, Schuyler W.; Tayler, Rachel
Abstract : There has been a recent surge in the number of children migrating to the United States without a parent. Despite their vulnerability to extreme adversity at every stage of their migration process, little is known about the psychosocial context and mental health needs of unaccompanied children. This article presents a case study of a 16‐year‐old Salvadoran boy who participated in a larger, mixed‐methods study on the psychosocial context, psychological presentation, and mental health service utilization of unaccompanied children living in New York pending their immigration cases. After the presentation of the case, different models for understanding the experiences and needs of unaccompanied children are discussed.